A Naturalistic Comparison of Group Transdiagnostic Behaviour Therapy (TBT) and Disorder-Specific Cognitive Behavioural Therapy Groups for the Affective Disorders. Issue 1 (29th May 2018) - Gros, Daniel F.; Merrifield, Colleen; Rowa, Karen; Szafranski, Derek D.; Young, Lisa; McCabe, Randi E.
Abstract : Background: Transdiagnostic psychotherapies are designed to apply the same underlying treatment principles across a set of psychiatric disorders, without significant tailoring to specific diagnoses. Several transdiagnostic psychotherapy protocols have been developed recently, each of which has its own strengths and weaknesses. One promising treatment is Transdiagnostic Behaviour Therapy (TBT), in that it is one of the few transdiagnostic treatments to date shown to be effective in patients with depressive and anxiety disorders. However, TBT has only been investigated via individual psychotherapy.Aims: The present study investigated the effectiveness of a group protocol for TBT, compared with disorder-specific group psychotherapies, in a naturalistic setting.Method: 109 participants with various diagnoses of affective disorders completed either group TBT ( n = 37) or a disorder-specific group psychotherapy ( n = 72). Measures included assessments of psychiatric symptomatology and transdiagnostic impairment at baseline and post-treatment.Results: Overall, participants in the TBT group demonstrated significant improvements across all measures. When compared with disorder-specific groups, no statistical differences were observed between groups across symptoms; however, participants in the TBT group demonstrated roughly twice the treatment effect sizes in transdiagnostic impairment compared with participants in the disorder-specific groups. In addition, when participants from the most well-represented diagnosis and disorder-specific treatment (social anxiety disorder) were investigated separately, participants in the TBT group demonstrated significantly larger improvements in comorbid depressive symptoms than participants in the disorder-specific treatment.Conclusions: Pending replication and additional comparison studies, group TBT may provide an effective group treatment option for patients with affective disorders.